Clostridium perfringens Epsilon Toxin: A Malevolent Molecule for Animals and Man? - Stiles, Bradley G. (MDPI, 2013)
Clostridium perfringens is a prolific, toxin-producing anaerobe causing multiple diseases in humans and animals. One of these toxins is epsilon, a 33 kDa protein produced by Clostridium perfringens (types B and D) that induces fatal enteric disease of goats, sheep and cattle. Epsilon toxin (Etx) belongs to the aerolysin-like toxin family. It contains three distinct domains, is proteolytically-activated and forms oligomeric pores on cell surfaces via a lipid raft-associated protein(s). Vaccination controls Etx-induced disease in the field. However, therapeutic measures are currently lacking. This review initially introduces C. perfringens toxins, subsequently focusing upon the Etx and its biochemistry, disease characteristics in various animals that include laboratory models (in vitro and in vivo), and finally control mechanisms (vaccines and therapeutics).